2013
DOI: 10.1371/journal.pone.0079144
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcode Identification of Freshwater Snails in the Family Bithyniidae from Thailand

Abstract: Freshwater snails in the family Bithyniidae are the first intermediate host for Southeast Asian liver fluke (Opisthorchis viverrini), the causative agent of opisthorchiasis. Unfortunately, the subtle morphological characters that differentiate species in this group are not easily discerned by non-specialists. This is a serious matter because the identification of bithyniid species is a fundamental prerequisite for better understanding of the epidemiology of this disease. Because DNA barcoding, the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Previous studies have reported approximately 30 species of eight freshwater snail families infected by trematode cercariae in Thailand: Ampullariidae, Bithyniidae, Lymnaeidae, Nassariidae, Pachynidae, Planorbidae, Thiaridae and Viviparidae (Dechruksa et al, 2007;Ukong et al, 2007;Chuboon and Wongsawad, 2009;Chontananarth and Wongsawad, 2013;Krailas et al, 2014;Kulsantiwong et al, 2015;Namsanor et al, 2015;Anucherngchai et al, 2016Anucherngchai et al, , 2017Veeravechsukij et al, 2018), these studies have revealed 15 morphological types of trematode cercariae, such as amphistome, echinostome, gymnocephalous, parapleurolophocercous, pleurolophocercous and xiphidiocercariae, which belong to families of human intestinal flukes (Chai et al, 2009;Hung et al, 2013;Chai, 2019). Moreover, nine families of brackish-water snails have been observed to carry cercariastage digenean trematodes (Sri-Aroon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported approximately 30 species of eight freshwater snail families infected by trematode cercariae in Thailand: Ampullariidae, Bithyniidae, Lymnaeidae, Nassariidae, Pachynidae, Planorbidae, Thiaridae and Viviparidae (Dechruksa et al, 2007;Ukong et al, 2007;Chuboon and Wongsawad, 2009;Chontananarth and Wongsawad, 2013;Krailas et al, 2014;Kulsantiwong et al, 2015;Namsanor et al, 2015;Anucherngchai et al, 2016Anucherngchai et al, , 2017Veeravechsukij et al, 2018), these studies have revealed 15 morphological types of trematode cercariae, such as amphistome, echinostome, gymnocephalous, parapleurolophocercous, pleurolophocercous and xiphidiocercariae, which belong to families of human intestinal flukes (Chai et al, 2009;Hung et al, 2013;Chai, 2019). Moreover, nine families of brackish-water snails have been observed to carry cercariastage digenean trematodes (Sri-Aroon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the endemic regions of northeast Thailand, there is a high prevalence of O . viverrini infection in humans and fish, although the prevalence of infected Bithynia snails is low [6–10]. It has been found that the level of O .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the difficulty in breeding snails in the laboratory, wild snails were collected from the field and checked for parasitic infections. Uninfected snails were infected with O. viverrini eggs and the infection was monitored by cercarial emission and examination of hatched eggs in the snail faeces twice each week over an 8 week period as described previously [9, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…The plastic containers were checked daily and dead snails were removed. Each snail was subsequently examined for trematode infection by testing cercarial shedding and examination of hatched eggs in the snail faeces twice within a week as described previously [9, 30]. …”
Section: Methodsmentioning
confidence: 99%